UNCONVENTIONAL HYDROCARBON RESOURCES: GEOLOGICAL AND ECONOMIC EVALUATION - Mikhailov , V.; Kurilo, M.; Andreeva, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The paper considers the issue of geological and economic evaluation of unconventional hydrocarbon resources – shale gas, namely. The purpose of the work is to review the methods employed to estimate and evaluate hydrocarbon reserves, with factors and criteria to be determined. The material studied reveals most methods to have been mainly devised to estimate traditional hydrocarbons – volumetric method, namely. The paper proposes a fundamental formula for shale gas resource evaluation. Additional criteria for quantitative evaluation of the unconventional gas resources in the compacted rocks are also characterized. The paper provides factors, both regional and local ones, necessary to estimate hydrocarbons probability on the tectonic site. There is grounded a fill factor to be a quantitative index to hydrocarbon traps. Hydrocarbon trap saturation coefficients for effective pays of the DnieperDonets Basin are stated. The indices mentioned above are proposed to be considered an additional factor when modifying resource estimators. The paper examines other factors affecting the evaluation of shale gas resources. It reviews basic technologies used to produce unconventional hydrocarbons, with mining technologies to be involved in traditional evaluations. Fracturing coefficient is supposed to be an important factor for unconventional hydrocarbons, which largely affects the properties of collector rocks. Perspective area index differentiated on the complexity of the geological structure is proposed to be also taken into account. Probability factor is traditionally considered in the state-of-theart technologies as an indicator of shale gas presence, which indices for different regions of the world and the Dnieper-Donetsk region are given in the paper. The fill factor, fracturing coefficient, perspective area coefficient differentiated on the complexity of the geological structure, probability factor are proposed to be applied as additional factors when evaluating shale gas resources. The paper shows estimates on shale gas resources in the eastern petroleum region of Ukraine and sets objectives of further research into unconventional hydrocarbon resources in the country.